Metal pollution resistant catalytic cracking aid and preparation method thereof
By using an anti-metal pollution catalytic cracking additive containing phosphorus, alumina nanofibers, flake aluminum phosphate, titanium modified clay, aluminum compounds and alkaline earth metal compounds, we can trap and passivate metal pollutants such as iron, nickel, vanadium and other metal pollutants that appear during catalytic cracking, the problem of catalyst poisoning and inactivation is solved, and the selectivity and product yield of the catalytic cracking reaction are improved.
Patent Information
- Application Number
- CN202311423239.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-10-30
AI Technical Summary
During catalytic cracking, metal pollutants such as iron, nickel, vanadium are deposited on the catalyst, resulting in catalyst poisoning and inactivation, affecting the selectivity of the catalytic cracking reaction and product yield.
A catalytic cracking additive with anti-metal pollution is used, and its composition includes phosphorus, aluminum oxide nanofibers, sheet aluminum phosphate, titanium modified clay, aluminum compounds and alkaline earth metal compounds. These components capture and passivate the contaminated metals such as iron, nickel, vanadium, etc. in the raw oil to form stable compounds and reduce their deposition on the catalyst.
It effectively reduces the harmful effects of metal iron, nickel and vanadium on catalysts, improves the selectivity and product yield of catalytic cracking reactions, and extends the service life of the catalyst.
Smart Images

Figure BDA0004522174330000151 
Figure BDA0004522174330000161 
Figure HDA0004522174550000011
Abstract
Description
Technical Field
[0001] The invention belongs to the field of oil refining catalysts and additives, and relates to a catalytic cracking additive, in particular to a catalytic cracking additive resistant to iron, nickel, vanadium, especially iron pollution and a preparation method thereof. Background Art
[0002] In the process of industrial production of polyolefins, the widely used catalyst is mainly Ziegler-Natta catalyst, which is a titanium catalyst. Regarding the preparation of titanium polyolefin catalysts, for example, patent CN102336851B discloses a propylene polymerization catalyst, including magnesium, titanium, halogen and internal electron donor compounds diisobutyl phthalate, diethyl phthalate or di-n-butyl phthalate and a mixture of succinate; patent CN107434832B discloses a propylene polymerization catalyst, mainly composed of alcohol magnesium compounds, titanium compounds and phosphate electron donor compounds. The common method for preparing titanium catalysts at present is: firstly prepare magnesium halide alcohol compound, for example, after magnesium halide and alcohol are heated and dissolved, high pressure ejection or high speed stirring is used, and the method of solidifying into microsphere particles in a cooling medium is obtained, and the specific steps are referred to the relevant description in CN1110281A; then the magnesium halide alcohol compound particles are reacted with halogen-containing compounds such as titanium tetrachloride to prepare a magnesium-supported catalyst, during which various promoters can be added for modification. In the above-mentioned catalyst preparation process, a large amount of titanium tetrachloride needs to be used, and the excess ratio is very large. At the same time, the solid catalyst component obtained needs to be washed with a hydrocarbon solvent (such as hexane) to remove the titanium tetrachloride not loaded therein. Therefore, in the polyolefin catalyst production process, after the catalyst solid is separated and precipitated, a large amount of catalyst mother liquid containing at least one of titanium tetrachloride, unreacted hydrocarbons, unreacted halogenated alkoxy titanium, alkoxy magnesium, and unreacted esters will be produced. The titanium tetrachloride waste liquid generated in the titanium polypropylene catalyst preparation process contains, in addition to titanium tetrachloride (at least 80% or more), a small amount of alkoxy titanium complex (for example, about 2%-5%), a small amount of lipids, and n-hexane. If the waste liquid is directly discarded, it is bound to cause environmental pollution and waste of resources, so it needs to be effectively utilized.
[0003] Catalytic cracking feedstock contains metal pollutants such as iron, nickel, and vanadium. These metal pollutants are deposited on the catalyst during the catalytic cracking process, causing catalyst poisoning and deactivation, making the catalytic cracking reaction selectivity worse, increasing the yield of coke and dry gas, and reducing the yield of target products such as gasoline and diesel, affecting the smooth operation of the catalytic cracking unit and the economic benefits of the refinery. As FCC feedstocks become heavier and inferior, the impact of metal poisoning on FCC catalysts is becoming more and more serious. Among them, iron will be deposited on the catalyst surface, forming a low-melting point eutectic with sodium and silicon in the catalyst, blocking the pores of the catalyst, affecting the diffusion and mass transfer of oil and gas molecules in the catalyst pores, reducing the accessibility of the catalyst active center, thereby reducing the heavy oil conversion ability of the catalyst and deteriorating the selectivity of the catalytic cracking reaction; vanadium in the feedstock oil will form vanadic acid under FCC conditions, causing dealumination and structural collapse of the molecular sieve framework, and ultimately causing the deactivation of the molecular sieve and the catalyst, thereby also reducing the heavy oil conversion ability of the catalyst and deteriorating the selectivity of the catalytic cracking reaction; nickel in the crude oil is deposited on the catalyst. During the catalytic cracking reaction, nickel has a strong dehydrogenation activity, which increases the hydrogen yield, and promotes the coking of the unsaturated hydrocarbon polycondensation reaction to block the catalyst pores, reduce the specific surface area of the catalyst, and deteriorate the selectivity of the catalyst cracking reaction.
[0004] In view of the adverse effects of metal pollutants such as iron, nickel, and vanadium on catalysts, current technologies mainly focus on improving the ability of catalytic cracking catalysts to resist metal pollution, using catalytic cracking aids, and using metal passivators. Among them, the use of catalytic cracking aids and metal passivators is easy to use, does not require the replacement of all catalysts in the catalytic cracking unit in order to achieve a certain reaction target, and has the characteristics of small dosage and quick effect.
[0005] In terms of metal pollution-resistant catalysts, CN1057022C discloses a zeolite catalyst with chemically modified matrix and its preparation method, using alkaline earth metal titanate and phosphorus-containing γ-Al2O3 as a new component of the catalyst matrix. The catalyst is composed of 10-60% by weight of one of HY, REY, and USY zeolites, 5-40% by weight of natural or synthetic kaolin, 5-40% by weight of high temperature resistant γ-Al2O3 containing 0.1-4.0% by weight of phosphorus, and 1-30% by weight of alkaline earth metal titanate selected from Ba, Sr, and Mg. The catalyst has high activity, high carbon resistance, and strong resistance to heavy metal nickel and vanadium pollution.
[0006] CN104014361B discloses a catalytic cracking catalyst and a preparation method thereof. The catalyst comprises 1-60 wt% of modified dual-pore distribution alumina, 10-70 wt% of molecular sieve with FAU structure, 1-60 wt% of binder and 5-70 wt% of clay; based on the weight of the modified dual-pore distribution alumina, the modified dual-pore distribution alumina contains 0.05-1 wt% of rare earth calculated as RE2O3 and 0.5-10 wt% of silicon calculated as SiO2; the modified dual-pore distribution alumina has a crystalline phase structure of γ-alumina, the accessible pore size of the pores with smaller pore size is 4-9.5 nm, the accessible pore size of the pores with larger pore size is 12-25 nm, and the specific surface area is 250-500 m 2 / g, pore volume is 0.6-1.8cm 3 / g. The catalyst can improve gasoline quality and increase the yield of liquid products, and has a strong heavy oil cracking ability under the condition of metal contamination.
[0007] CN103769192B discloses a catalytic cracking catalyst and a preparation method thereof. The catalyst contains a silicon-aluminum material with a dual pore distribution and a molecular sieve. The accessible pore size of the smaller pores of the silicon-aluminum material with a dual pore distribution is 2-10nm, and the accessible pore size of the larger pores is 10-25nm. Based on the total amount of the catalyst, the content of the silicon-aluminum material with a dual pore distribution is 1-52%, the content of clay is 9-60%, the content of phosphorus is 0-8% in terms of P2O5, the content of rare earth metal is 0-3% in terms of RE2O3, the content of binder is 19-70%, and the content of Y-type molecular sieve is 20-70%. The catalyst has strong metal pollution resistance, strong heavy oil cracking ability, high liquid yield, and can improve the quality of gasoline in cracking products.
[0008] In terms of anti-metal pollution additives, CN100478420C discloses a catalytic cracking additive and a preparation method thereof, wherein the additive contains alumina and molecular sieves, with or without clay, wherein the alumina is η-alumina and / or X-alumina, or a mixture of η-alumina and / or X-alumina and γ-alumina, and the additive also contains phosphorus and alkaline earth metals, and based on the weight of the additive, the content of η-alumina and / or X-alumina is 0.5-50% by weight, the content of γ-alumina is 0-50% by weight, the content of molecular sieve is 0.5-20% by weight, the content of clay is 0-75% by weight, the content of phosphorus is 0.1-4% by weight in terms of P2O5, the content of alkaline earth metal is 0.1-4% by weight in terms of oxides, and the molecular sieve is Y-type zeolite. The additive has a strong ability to resist heavy metal pollution and can improve the quality of gasoline in cracking products.
[0009] CN101439303A discloses a heavy hydrocarbon oil catalytic cracking aid and a preparation method thereof, comprising the following components (wt%): Al2O3 10-65%, P (in terms of P element) 2-13%, SiO2 1-15%, and clay 10-65%. The preparation method of the aid comprises: a. Preparation of phosphatic aluminum gel: dissolving a phosphorus source compound and hydrated aluminum oxide in deionized water according to a molar ratio of P:Al2O3=0.5-5:1, and preparing a phosphatic aluminum gel with a solid content of 20-40wt%; stirring and peptizing at a temperature of 20℃-60℃ for 1-5h; preparing the phosphatic aluminum gel for standby use; b. Preparation of silicon phosphatic aluminum gel: adding water glass to the peptized phosphatic aluminum gel, wherein the amount of water glass added is calculated in weight percentage. The ratio is SiO2:Al2O3=0.01-1.5:1, and the mixture is aged at 20℃-80℃ for 1-3h under stirring; silicon-phosphorus-aluminum gel is obtained and set aside; c. Mixing and beating: clay is added to the silicon-phosphorus-aluminum gel, and the amount of clay added makes the clay content in the final additive 10-65wt%, and the mixture is mixed and beated for 1-3 hours; d. Spray forming; e. Washing and drying: washing with deionized water until the filtrate has a pH value between 6-7, and drying at 80-120℃. The additive has a strong ability to resist heavy metal staining and improves the selectivity of heavy hydrocarbon oil cracking reaction. However, the patent does not provide the effect of the additive on resisting heavy metal pollution, nor does it specify which heavy metal pollution the additive resists. The presence of silicon oxide is not conducive to anti-iron pollution. The additive contains SiO2 provided by water glass, and iron oxide forms a low-melting point eutectic with sodium and silicon oxide with a melting point below 500°C. It has strong fluidity under the reaction-regeneration temperature conditions, blocking the catalyst pores, preventing the diffusion of macromolecules, affecting the accessibility of the catalyst active center, and reducing the heavy oil conversion capacity (Document 1: Shi Lei, Bi Lintian, Yao Yuan. Effect of iron on catalytic cracking catalysts [J]. Qilu Petrochemical, 2012, 40(1): 50-53; Document 2: Bai Rui. Research on the migration law of iron in the bed of catalytic cracking reactor and the industrial application of new iron-resistant catalysts [J]. Petroleum Refining and Chemical Industry, 2022, 53(4): 38-42).
[0010] In terms of anti-metal contamination passivators, CN88102585A discloses a method for inhibiting the poisoning effect of polluting metals on cracking catalysts in fluidized catalytic cracking processes, wherein a small amount of bismuth-containing passivator is deposited on the catalyst to inhibit the poisoning of polluting metals such as nickel, vanadium and iron on cracking catalysts in the fluidized catalytic cracking process of hydrocarbon feeds containing polluting metals. Ideally, the weight ratio of bismuth to nickel equivalent (nickel + 0.2 vanadium and 0.1 iron) is about 0.01:1-1:1. The passivator may also contain a mixture of bismuth and antimony and bismuth and tin compounds.
[0011] CN100540141C discloses a catalytic cracking metal passivator and a preparation method thereof, which provides a compound containing boron or boron and phosphorus as a catalytic cracking metal passivator. The passivator has a significant passivation effect on nickel on the catalytic cracking catalyst, and the distribution of the reaction products is significantly improved, the yield of the ideal product gasoline is increased by 2.5 to 4 percentage points, the yield of the non-ideal products coke and hydrogen is reduced, and the yield of hydrogen is reduced by 20-40%. However, if boron migrates to the catalyst, even a small amount of boron will destroy the structure of the active component molecular sieve in the catalyst, causing the cracking activity and conversion rate of the catalyst to decrease.
[0012] CN1133717C discloses a water-soluble catalytic cracking (FCC) metal passivator and its preparation method. The passivator is effective against heavy metal pollution on catalytic cracking catalysts, especially pollution of nickel, iron, vanadium and sodium. The agent uses antimony, aluminum and rare earth metal element lanthanum (or cerium) as main active components. The compounds of these metal elements react with organic carboxylic acids and then mix to form highly stable compounds. The agent has the characteristics of high efficiency, low toxicity, stable properties (no decomposition below 300°C), easy use, and miscible with water. It can passivate the pollution of nickel, iron, vanadium and sodium on the catalyst, improve the yield of gasoline and light oil, reduce the hydrogen yield and hydrogen / methane, improve product selectivity, and improve catalyst activity.
[0013] In the prior art, the catalytic cracking catalysts resistant to metal pollution generally contain metal capture components, such as rare earth oxides, alkaline earth metals, etc., in the formulation design, and use porous active carrier materials or change the catalyst preparation technology to increase the pore volume and medium and large pore ratio of the catalyst, which can passivate heavy metals, reduce the side effects of metal pollution on the catalyst, and improve the catalyst's ability to resist metal pollution. However, the rare earth oxides and alkaline earth metals used to capture metals in the catalyst will be transferred to the molecular sieve during use, among which the rare earth will increase the acid density of the molecular sieve catalyst and the coke yield, and too much alkaline earth metal will neutralize the acid active center of the molecular sieve, causing the catalyst activity to decrease. Therefore, the content of rare earth and alkaline earth metals used to resist metal pollution in the catalytic cracking catalyst is usually low, affecting its anti-metal pollution effect.
[0014] In the prior art, the passivator for resisting metal pollution is in liquid phase, generally containing organic solvent and metal capture component, wherein the metal capture component is such as Sb, rare earth oxide, alkaline earth metal, etc. In the catalytic cracking process, the passivator is added into the reactor along with the raw oil, and the passivator droplets are deposited on the surface of the catalyst microspheres, and react with the harmful polluting metal components, thereby passivating the heavy metals, reducing the side effects of metal pollution on the catalyst, and improving the catalyst's ability to resist metal pollution. However, the metal passivators with industrial application value mainly include organic metal passivators such as antimony type, bismuth type and tin type, which are highly toxic and harmful to the human body and the environment, limiting their use; in addition, the stability of the passivator will also affect its performance.
[0015] Therefore, in order to reduce the adverse effects of metal pollutants such as iron, nickel, and vanadium contained in catalytic cracking feedstock on catalysts, despite the recent technologies of catalysts, additives, and metal passivators, new technologies for preparing additives that are environmentally friendly, simple and feasible, and have excellent resistance to pollution by metals such as iron, nickel, and vanadium are still needed. Summary of the invention
[0016] In order to solve the above problems, the purpose of the present invention is to provide a metal pollution resistant catalytic cracking aid and a preparation method thereof. The metal pollution resistant catalytic cracking aid has good metal pollution resistance, cracking reaction selectivity and use performance.
[0017] In order to achieve the above object, the present invention provides a metal pollution resistant catalytic cracking aid, which comprises, based on the weight of the metal pollution resistant catalytic cracking aid being 100%, 4-40% phosphorus calculated as P2O5, 1-15% alumina nanofibers calculated on a dry basis, 1-10% flaky aluminum phosphate calculated on a dry basis, 2-50% titanium modified clay, 0-30% aluminum compounds calculated on an oxide basis, 0-20% alkaline earth metals calculated on an oxide basis, 0-70% clay calculated on a dry basis, and 0-10% inorganic carrier materials calculated on an oxide basis; wherein the preparation method of the titanium modified clay comprises the following steps:
[0018] (1) mixing calcined clay, water and titanium tetrachloride solution to obtain a mixture; (2) reacting the mixture at 40-120° C. for 0.5-6 hours to obtain the titanium-modified clay; based on the dry basis of the titanium-modified clay being 100%, the composition of the titanium-modified clay comprises 7-45wt% titanium calculated as oxide, 0.6-40wt% aluminum calculated as oxide, and 30-92wt% silicon calculated as oxide.
[0019] According to a specific embodiment of the present invention, preferably, based on the weight of the anti-metal pollution catalytic cracking aid being 100%, its composition comprises: 10-30% phosphorus calculated as P2O5, 3-15% alumina nanofibers calculated on a dry basis, 3-8% flaky aluminum phosphate calculated on a dry basis, 5-20% titanium-modified clay, 5-25% aluminum compounds calculated on an oxide basis, 1-10% alkaline earth metals calculated on an oxide basis, 5-62% clay calculated on a dry basis, and 0-8% inorganic carrier materials calculated on an oxide basis.
[0020] According to a specific embodiment of the present invention, preferably, the solid content of the titanium-modified clay is 10-45 wt %.
[0021] According to a specific embodiment of the present invention, preferably, based on 100% dry weight of the titanium-modified clay, the composition of the titanium-modified clay comprises 7-30 wt % titanium calculated as oxide, 8-40 wt % aluminum calculated as oxide, and 35-70 wt % silicon calculated as oxide.
[0022] According to a specific embodiment of the present invention, preferably, in the method for preparing the titanium-modified clay, the mixed raw materials also include a dispersant; based on the dry basis of the titanium-modified clay as 100%, the content of the dispersant is less than 10%, more preferably 0.3-5%.
[0023] According to a specific embodiment of the present invention, preferably, the dispersant includes one or a combination of two or more of 1,3,5-trimethylbenzene, 1,3,5-triisopropylbenzene, methyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, and polyethylene glycol.
[0024] According to a specific embodiment of the present invention, preferably, in the method for preparing titanium-modified clay, the titanium tetrachloride solution is titanium tetrachloride waste liquid; the titanium tetrachloride waste liquid is a waste liquid containing titanium tetrachloride generated during the preparation of a polypropylene catalyst.
[0025] According to a specific embodiment of the present invention, preferably, in the method for preparing the titanium-modified clay, the titanium tetrachloride solution is pure titanium tetrachloride.
[0026] According to a specific embodiment of the present invention, preferably, in the method for preparing the titanium-modified clay, the clay comprises one or a combination of two or more of kaolin, halloysite, montmorillonite, diatomaceous earth, halloysite, sepiolite and bentonite.
[0027] According to a specific embodiment of the present invention, preferably, in the method for preparing the titanium-modified clay, the calcination is performed at 400-900° C. for 0.5-6 h.
[0028] According to a specific embodiment of the present invention, preferably, the method for preparing the titanium-modified clay comprises the following steps: mixing clay calcined at 550-850°C for 1-3h, water, and waste liquid containing titanium tetrachloride to form a mixture, heating the mixture to 60-120°C and reacting for 0.5-3h to obtain the titanium-modified clay.
[0029] According to a specific embodiment of the present invention, preferably, in the method for preparing titanium-modified clay, after the reaction in step (2) is completed, the pH value of the reaction system is 0.5-8; more preferably, an alkaline substance is used to adjust the pH value of the reaction system to 0.5-8; more preferably, the alkaline substance is selected from one or a combination of two or more of ammonia water, ammonium carbonate, ammonium bicarbonate, water glass, sodium aluminate, magnesium oxide, magnesium hydroxide, magnesium carbonate, calcium oxide, calcium hydroxide, and calcium carbonate.
[0030] According to a specific embodiment of the present invention, preferably, in step (1), the clay is crushed to an average particle size D (v, 0.5) < 4 μm before or after calcination, and then mixed with water and titanium tetrachloride solution.
[0031] According to a specific embodiment of the present invention, preferably, the phosphorus comes from one or a combination of two or more of phosphoric acid, phosphates, phosphorous acid, phosphites, pyrophosphate, pyrophosphate, polyphosphoric acid, polyphosphate, metaphosphoric acid, and metaphosphates, and more preferably from one or a combination of two or more of phosphoric acid, ammonium phosphate, ammonium hydrogen phosphate, diammonium hydrogen phosphate, magnesium phosphate, aluminum phosphate, phosphorous acid, ammonium phosphite, sodium pyrophosphate, sodium tripolyphosphate, and sodium hexametaphosphate.
[0032] According to a specific embodiment of the present invention, preferably, the diameter of the alumina nanofiber is 20-100 nm, the length is 0.1-5 μm, and the specific surface area is ≥400 m 2 / g, pore volume ≥1.5cm 3 / g.
[0033] According to a specific embodiment of the present invention, preferably, the preparation method of the flaky aluminum phosphate is: react an aluminum compound and a phosphorus compound at a molar ratio of P / Al=(2.6-3.4):1 at 40°C-90°C for 0.1-1h, then react at 120°C-170°C for 0.5-3h, dry, and calcine at 400°C-700°C for 0.5-3h to obtain the flaky aluminum phosphate.
[0034] According to a specific embodiment of the present invention, preferably, the aluminum compound includes one or a combination of two or more of aluminum oxide, aluminum hydroxide, aluminum sol, and pseudo-boehmite.
[0035] According to a specific embodiment of the present invention, preferably, the phosphorus compound includes one or a combination of two or more of phosphoric acid, phosphates, phosphorous acid, phosphites, pyrophosphoric acid, pyrophosphates, polyphosphoric acid, polyphosphates, metaphosphoric acid, and metaphosphates, and more preferably one or a combination of two or more of phosphoric acid, ammonium phosphate, ammonium hydrogen phosphate, diammonium hydrogen phosphate, phosphorous acid, and ammonium phosphite.
[0036] According to a specific embodiment of the present invention, preferably, the clay comprises one or a combination of two or more of kaolin, halloysite, montmorillonite, halloysite, and pyrophyllite bentonite, more preferably one or a combination of two or more of kaolin, halloysite, and halloysite.
[0037] According to a specific embodiment of the present invention, preferably, the aluminum compound includes one or a combination of two or more of pseudo-boehmite, boehmite, amorphous alumina, and aluminum sol, but does not include alumina nanofibers.
[0038] According to a specific embodiment of the present invention, preferably, the alkaline earth metal includes one or a combination of two or more of magnesium, calcium and barium.
[0039] According to a specific embodiment of the present invention, preferably, the alkaline earth metal is one or a combination of two or more of the oxides, chlorides, nitrates, carbonates, oxalates and acetates of magnesium, calcium and barium.
[0040] According to a specific embodiment of the present invention, preferably, the inorganic carrier material includes one or a combination of two or more of zirconium oxide, chloride, nitrate, carbonate, sulfate, oxalate and acetate.
[0041] According to a specific embodiment of the present invention, preferably, the composition of the anti-metal pollution catalytic cracking aid also includes a pore structure improver; the weight of the pore structure improver is less than 10% (more preferably 0.5-6%) of the total weight of the anti-metal pollution catalytic cracking aid, so as to improve the dispersibility of the colloid during the preparation of the aid and improve the pore structure, specific surface area and other properties of the aid.
[0042] According to a specific embodiment of the present invention, preferably, the pore structure improver includes one or a combination of two or more of 1,3,5-trimethylbenzene, 1,3,5-triisopropylbenzene, methyl cellulose, polyvinyl alcohol, and polyethylene glycol. More preferably, the methyl cellulose is hydroxymethyl cellulose and / or carboxymethyl cellulose.
[0043] The present invention also provides a method for preparing the above-mentioned anti-metal pollution catalytic cracking aid, which comprises the following steps: (1) mixing and slurrying a phosphorus compound, alumina nanofibers, flaky aluminum phosphate, titanium-modified clay, an aluminum compound, an alkaline earth metal compound, clay, and an inorganic carrier material (preferably with a pore structure improver) to obtain a slurry; (2) spray-drying the slurry to form it, and then calcining and curing it to obtain the anti-metal pollution catalytic cracking aid.
[0044] According to a specific embodiment of the present invention, preferably, the flaky aluminum phosphate in step (1) is sand-milled before mixing and beating and / or the slurry in step (2) is sand-milled before spray drying, so that the average particle size D (v, 0.5) of the flaky aluminum phosphate in step (1) and / or the slurry in step (2) is less than 4 μm.
[0045] According to a specific embodiment of the present invention, preferably, the pseudo-boehmite is treated with acid and then aged at 40-90°C for 0.5-3 hours for peptization before use, or is subjected to aging treatment after mixing with other components; in the process of acid-peptization of the pseudo-boehmite, the acid is an inorganic acid, such as one or a combination of two or more of hydrochloric acid, sulfuric acid, and nitric acid.
[0046] The present invention does not limit the spray drying method, and the technology known to those skilled in the art can be used, and the process conditions are, for example, the spray tower furnace temperature is controlled at 450-550° C., and the spray tail gas temperature is controlled at 200-300° C. The present invention can control the screening distribution of the spray-formed catalyst microspheres by controlling the spray forming conditions such as the spray pressure and the nozzle size.
[0047] The metal pollution-resistant catalytic cracking additive of the present invention reduces the harmful effects of metal iron, nickel and vanadium on the catalyst through the following design schemes: (1) phosphorus compounds, titanium-modified clay, aluminum compounds and alkaline earth metal compounds are used to capture and passivate polluting metals such as iron, nickel and vanadium in the raw oil, so that the polluting metals form stable compounds with the phosphorus compounds, titanium-modified clay, aluminum compounds and alkaline earth metal compounds in the additive, reducing their deposition on the catalyst, thereby maintaining the excellent cracking reaction performance and use performance of the catalyst; (2) the additive does not contain Y-type molecular sieves, which can avoid a large amount of phosphorus, alkali metals and vanadium. The adverse effects of earth metals on the structure of molecular sieves and the selectivity of cracking reactions are reduced, and the capture and passivation effects of phosphorus and alkaline earth metals on pollutant metals are fully guaranteed; (3) The additive does not contain rare earths, avoiding the formation of stable rare earth phosphates between phosphorus and rare earths, thereby reducing the capture and passivation effects of phosphorus on iron, nickel and vanadium; in addition, long rod-shaped alumina nanofibers, flaky aluminum phosphates, titanium-modified clays and pore structure improvers with different morphological characteristics build a smooth pore structure in the additive, which can improve the dispersibility of the colloid during the preparation of the additive, and improve the additive's pore structure, specific surface area and heavy metal passivation effect and other properties.
[0048] The auxiliary agent provided by the present invention has a simple preparation process and is environmentally friendly, and does not contain elements such as antimony, bismuth and tin that are harmful to the human body and are used in conventional metal passivators; the content of phosphorus compounds, titanium-modified clay, aluminum compounds and alkaline earth metal compounds in the auxiliary agent can be adjusted within a larger range, so that the auxiliary agent can fully exert its anti-metal pollution performance without affecting the activity and reaction performance of the main catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 is an appearance diagram of the flaky aluminum phosphate in Example 1;
[0050] Figure 2 is a SEM image of the flaky aluminum phosphate in Example 1;
[0051] Figure 3 is the SEM image of alumina nanofibers. DETAILED DESCRIPTION
[0052] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0053] The element contents of the following sample catalysts and additives were determined by X-ray fluorescence analysis. The wear index of the catalyst was analyzed by the MS-C / 6 wear index analyzer produced by Shenyang Kehui Instrument Manufacturing Co., Ltd. The pore volume of the catalyst was determined by the water drop method.
[0054] Origin and specifications of the following raw materials:
[0055] (1) Waste liquid containing titanium tetrachloride (hereinafter referred to as waste liquid containing titanium tetrachloride) generated during the preparation of polypropylene catalyst: titanium content 90% (in terms of TiCl4), alumina nanofibers ( Figure 3 As shown, the specific surface area is 625m 2 / g, pore volume 1.88cm 3 / g, alumina nanofibers are long rods with a length of 200-600nm): all provided by Lanzhou Chemical Research Center of PetroChina Petrochemical Research Institute; kaolin (burning loss 29wt%), halloysite (burning loss 16.6wt%), pseudo-boehmite (burning loss 36wt%), aluminum sol (containing 21.6wt% alumina), boehmite (burning loss 17.0%), REY zeolite (RE2O3 content 18.0wt%, minus 7%), USY zeolite (Na2O content 1.2wt%, no rare earth, minus 4%): all industrial products, collected from Lanzhou Petrochemical Company Catalyst Plant. LDO-70 industrial catalyst: industrial product, produced by Lanzhou Petrochemical Company Catalyst Plant.
[0056] (2) β-alumina trihydrate (ignition loss 36%): produced by Shandong Aluminum Company Research Institute.
[0057] (3) Magnesium chloride, magnesium oxide, calcium carbonate, phosphoric acid (concentration 85%), diammonium phosphate, zirconium oxide, iron cyclopentaneate, petroleum ether, 1,3,5-trimethylbenzene, polyethylene glycol, and carboxymethyl cellulose: all are chemical reagents.
[0058] (4) Hydrochloric acid: concentration 36%, chemical reagent.
[0059] The spray drying methods of the catalytic cracking aids of the following Examples 1-5 and Comparative Examples 1-3 adopt the following process conditions: the furnace temperature of the spray tower is controlled at 450°C, the spray tail gas temperature is controlled at 200°C, and the particle size range of the obtained catalytic cracking aid is 65-78 μm.
[0060] Example 1
[0061] This embodiment provides a metal pollution resistant catalytic cracking aid, and the preparation method thereof is as follows:
[0062] 1. Preparation of titanium modified clay:
[0063] The kaolin was calcined at 750°C for 2 hours to obtain a calcined material, 1674 g (dry basis) of the calcined material was crushed to an average particle size D (v, 0.5) < 4 μm, 5.16 L of decationized water was added and stirred, 332 g of waste liquid containing titanium tetrachloride and 18 g of polyethylene glycol were added, the temperature was raised to 70°C, stirred for 1 hour, the pH value was 3.5, and titanium-modified clay M-1 was obtained;
[0064] The composition of titanium-modified clay M-1 is: 93 wt% (dry basis) of kaolin calcined material, 7 wt% (titanium oxide basis) of titanium from waste liquid containing titanium tetrachloride, and the solid content of titanium-modified clay M-1 is 25 wt%;
[0065] 2. Preparation of flake aluminum phosphate:
[0066] 0.14 kg of pseudo-boehmite (dry basis) and 2.67 L of deionized water were added to a pulping tank for pulping, and then 0.955 kg of phosphoric acid was added, reacted at 80°C for 10 minutes, then reacted at 135°C for 1 hour, dried, and calcined at 600°C for 1.5 hours to obtain flaky aluminum phosphate PAl-1, which has the appearance as shown below: Figure 1 As shown, it has a fluffy appearance, and the SEM image is shown in Figure 2 , the morphology is flake-like;
[0067] 3. Preparation of anti-metal pollution catalytic cracking additives:
[0068] 1.59 kg of kaolin (dry basis), 0.24 kg of titanium-modified clay M-1 (dry basis), 0.24 kg of pseudo-boehmite (dry basis), 0.15 kg of sheet aluminum phosphate PAl-1 and 3.2 kg of deionized water were added to a pulping tank and stirred for 1 hour, then 8 mL of hydrochloric acid was added, stirred for 15 minutes, and aged at 50° C. for 2 hours. 0.877 kg of phosphoric acid, 0.24 kg of alumina nanofibers (dry basis), and 30 g of carboxymethyl cellulose were added, mixed and pulped for 1 hour, and the resulting slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, spray-dried, and calcined to obtain a catalytic cracking aid CAT-1.
[0069] The composition of the additive CAT-1 is: 53 wt% (dry basis) of kaolin, 8 wt% (dry basis) of titanium-modified clay M-1, 8 wt% (dry basis) of alumina nanofibers, 5 wt% (dry basis) of sheet aluminum phosphate PAl-1, 8 wt% of alumina from pseudo-boehmite, and 18 wt% of phosphorus pentoxide from phosphoric acid. The colloid solid content of the additive CAT-1 is 36%.
[0070] Example 2
[0071] This embodiment provides a metal pollution resistant catalytic cracking aid, and the preparation method thereof is as follows:
[0072] 1. Preparation of titanium modified clay:
[0073] The halloysite was crushed to an average particle size D (v, 0.5) < 4 μm, and calcined at 600° C. for 5 hours to obtain a calcined material. 1499 g (dry basis) of the calcined material was added with 7.3 L of decationized water and stirred, and 793 g of waste liquid containing titanium tetrachloride was added, the temperature was raised to 90° C., stirred for 2 hours, and the pH value was adjusted to 2.5 with ammonia water to obtain titanium-modified clay M-2;
[0074] The composition of titanium-modified clay M-2 is: 83.3 wt% (dry basis) of halloysite calcined material, 16.7 wt% (titanium oxide basis) of titanium from waste liquid containing titanium tetrachloride, and 18 wt% of solid content of titanium-modified clay;
[0075] 2. Preparation of anti-metal pollution catalytic cracking additives:
[0076] 0.96 kg of halloysite (dry basis), 1.2 kg of titanium-modified clay M-2 (dry basis), 0.3 kg of pseudo-boehmite (dry basis), 30 g of aluminum sol (alumina), 60 g of flaky aluminum phosphate PAl-1 (dry basis) and 1.5 kg of deionized water were added to a slurrying tank for slurrying, stirred for 0.5 hour, then 5 mL of hydrochloric acid was added, stirred for 1 hour, and aged at 40° C. for 1 hour. 0.486 kg of diammonium phosphate, 90 g of alumina nanofibers (dry basis), 30 g of polyethylene glycol, and 60 g of magnesium oxide were added, mixed and slurried for 1.5 hours, and the obtained slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, spray-dried, and calcined to obtain catalytic cracking aid CAT-2.
[0077] The composition of the additive CAT-2 is: 32 wt% (dry basis) of halloysite, 40 wt% (dry basis) of titanium-modified clay M-2, 3 wt% (dry basis) of alumina nanofibers, 2 wt% (dry basis) of sheet aluminum phosphate PAl-1, 10 wt% of alumina from pseudo-boehmite, 1 wt% of alumina from aluminum sol, 10 wt% of phosphorus pentoxide from diammonium phosphate, and 2 wt% of magnesium oxide. The colloid solid content of the additive CAT-2 is 28%.
[0078] Example 3
[0079] This embodiment provides a metal pollution resistant catalytic cracking aid, and the preparation method thereof is as follows:
[0080] 1. Preparation of titanium modified clay:
[0081] The kaolin and diatomaceous earth were crushed to an average particle size D (v, 0.5) < 4 μm, and calcined at 850° C. for 2.5 hours to obtain a calcined material. 900 g (dry basis) of the kaolin calcined material, 100.8 g (dry basis) of the diatomaceous earth calcined material, and 72 g of carboxymethyl cellulose were added with 2.0 L of decationized water and stirred, and 2109 g of waste liquid containing titanium tetrachloride was added, the temperature was raised to 60° C., stirred for 3 hours, and the pH value was adjusted to 3.0 with ammonia water to obtain titanium-containing modified clay M-3;
[0082] The composition of titanium-modified clay M-3 is: 50 wt% (dry basis) of kaolin calcined material, 5.6 wt% (dry basis) of diatomaceous earth calcined material, 44.4 wt% (titanium oxide) of titanium from waste liquid containing titanium tetrachloride, and the solid content of titanium-modified clay M-3 is 30 wt%;
[0083] 2. Preparation of anti-metal pollution catalytic cracking additives:
[0084] 0.48 kg of kaolin (dry basis), 90 g of titanium-modified clay M-3 (dry basis), 0.24 kg of flaky aluminum phosphate PAl-1 (dry basis), 0.54 kg of pseudo-boehmite (dry basis), 1.525 kg of magnesium chloride and 3.3 kg of deionized water were added into a pulping tank and stirred for 2 hours. Then, 1.461 kg of phosphoric acid, 0.45 kg of alumina nanofibers (dry basis) and 60 g of 1,3,5-trimethylbenzene were added. After mixing and pulping for 0.5 hour, the obtained slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, spray-dried and calcined to obtain catalytic cracking aid CAT-3.
[0085] The composition of the additive CAT-3 is: 16 wt% (dry basis) of kaolin, 3 wt% (dry basis) of titanium-modified clay M-3, 15 wt% (dry basis) of alumina nanofibers, 8 wt% (dry basis) of sheet aluminum phosphate PAl-1, 18 wt% of aluminum oxide from pseudo-boehmite, 30 wt% of phosphorus pentoxide from phosphoric acid, and 10 wt% of magnesium oxide from magnesium chloride. The colloid solid content of the additive CAT-3 is 32%.
[0086] Example 4
[0087] This embodiment provides a metal pollution resistant catalytic cracking aid, and the preparation method thereof is as follows:
[0088] 0.72 kg of kaolin (dry basis), 0.75 kg of titanium-modified clay M-3 (dry basis), 0.12 kg of zirconium oxide, 0.54 kg of pseudo-boehmite (dry basis), 0.15 kg of boehmite (dry basis), 90 g of flaky aluminum phosphate PAl-1 (dry basis) and 3.8 kg of deionized water were added to a pulping tank for pulping. After stirring for 1 hour, 54 g of calcium carbonate, 0.15 kg of alumina nanofibers (dry basis), 0.731 kg of phosphoric acid and 120 g of carboxymethyl cellulose were added. After mixing and pulping for 2 hours, the resulting slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, spray-dried and calcined to obtain catalytic cracking aid CAT-4.
[0089] The composition of the additive CAT-4 is: 24 wt% (dry basis) of kaolin, 25 wt% (dry basis) of titanium-modified clay M-3, 5 wt% (dry basis) of alumina nanofibers, 3 wt% (dry basis) of sheet aluminum phosphate PAl-1, 4 wt% (dry basis) of zirconium oxide, 18 wt% of alumina from pseudo-boehmite, 5 wt% of alumina from boehmite, 15 wt% of phosphorus pentoxide from phosphoric acid, and 1 wt% of calcium oxide from calcium carbonate. The colloid solid content of the additive CAT-4 is 32%.
[0090] The pore volume of the additive CAT-4 measured by the water drop method is 0.30 mL / g.
[0091] Example 5
[0092] This embodiment provides a metal pollution resistant catalytic cracking aid, and the preparation method thereof is as follows:
[0093] 1. Preparation of flake aluminum phosphate:
[0094] 0.16 kg of pseudo-boehmite (dry basis) and 1.92 L of deionized water were added to a pulping tank for pulping, and then 0.955 kg of phosphoric acid was added, reacted at 60° C. for 20 minutes, then reacted at 160° C. for 0.5 h, dried, and calcined at 650° C. for 2 h to obtain flaky aluminum phosphate PAl-2;
[0095] 2. Preparation of titanium modified clay:
[0096] The kaolin was crushed to an average particle size D (v, 0.5) < 4 μm, and calcined at 850°C for 2 hours to obtain a calcined material. 1674 g (dry basis) of the calcined material was added to 5.19 L of decationized water and stirred, and 299 g of titanium tetrachloride and 9 g of polyethylene glycol were added. The temperature was raised to 85°C and stirred for 4 hours. The pH value was 3.6 to obtain titanium-containing modified clay M-4.
[0097] The composition of titanium-modified clay M-4 is: 93 wt% (dry basis) of kaolin calcined material, 7 wt% (titanium oxide basis) of titanium from titanium tetrachloride, and the solid content of titanium-modified clay M-4 is 25 wt%;
[0098] 3. Preparation of anti-metal pollution catalytic cracking additives:
[0099] 1.83 kg of kaolin (dry basis), 0.45 kg of titanium-modified clay M-4 (dry basis), 0.45 kg of pseudo-boehmite (dry basis), 30 g of sheet aluminum phosphate PAl-2 and 3.8 kg of deionized water were added to a slurrying tank and stirred for 1 hour, then 2.5 mL of hydrochloric acid was added, stirred for 20 minutes, and aged at 60° C. for 1 hour. 0.195 kg of phosphoric acid, 0.12 kg of alumina nanofibers (dry basis) and 15 g of carboxymethyl cellulose were added, mixed and slurried for 1 hour, and the obtained slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, spray-dried and calcined to obtain catalytic cracking aid CAT-5.
[0100] The composition of the additive CAT-5 is: 61 wt% (dry basis) of kaolin, 15 wt% (dry basis) of titanium-modified clay M-4, 4 wt% (dry basis) of alumina nanofibers, 1 wt% (dry basis) of sheet aluminum phosphate PAl-2, 15 wt% of alumina from pseudo-boehmite, and 4 wt% of phosphorus pentoxide from phosphoric acid. The colloid solid content of the additive CAT-5 is 32%.
[0101] Comparative Example 1
[0102] This comparative example provides a catalytic cracking aid, and its preparation method is as follows:
[0103] 1.71 kg of kaolin (dry basis), 0.12 kg of zirconium oxide, 0.54 kg of pseudo-boehmite (dry basis), 0.15 kg of boehmite (dry basis) and 4.9 kg of deionized water were added to a pulping tank for pulping. After stirring for 1 hour, 54 g of calcium carbonate and 0.731 kg of phosphoric acid were added. After mixing and pulping for 2 hours, the mixture was homogenized, spray-dried and calcined to obtain the comparison additive DCAT-1.
[0104] The composition of the additive DCAT-1 is: 57 wt% (dry basis) of kaolin, 4 wt% (dry basis) of zirconium oxide, 18 wt% of aluminum oxide from pseudo-boehmite, 5 wt% of aluminum oxide from boehmite, 15 wt% of phosphorus pentoxide from phosphoric acid, and 1 wt% of calcium oxide from calcium carbonate. The gelled solid content of the additive DCAT-1 is 32%.
[0105] The water drop method pore volume of the additive DCAT-1 is 0.20 mL / g.
[0106] Comparative Example 2
[0107] This comparative example provides a catalytic cracking aid, which is prepared according to the method of Example 1 of CN100478420C:
[0108] 1.05 kg of β-alumina trihydrate (dry basis), 120 g of USY zeolite (dry basis), 60 g of REY zeolite (dry basis), 1.713 kg of kaolin (dry basis), 183 g of magnesium chloride, 39 g of diammonium hydrogen phosphate and 4.6 kg of deionized water were added to a pulping tank and stirred for 1 hour to obtain a slurry with a solid content of 33 wt%. The slurry was homogenized and spray-dried into particles of 40-150 μm, and calcined at 500°C for 1 hour to obtain a comparative additive DCAT-2.
[0109] The composition of the additive DCAT-2 is: 57.1 wt% (dry basis) of kaolin, 35 wt% (dry basis) of β-alumina trihydrate, 4 wt% (dry basis) of USY zeolite, 2 wt% (dry basis) of REY zeolite, 0.7 wt% of phosphorus pentoxide from diammonium hydrogen phosphate, and 1.2 wt% of magnesium oxide from magnesium chloride. The gelled solid content of the additive DCAT-2 is 33%.
[0110] Comparative Example 3
[0111] This comparative example provides a catalytic cracking aid, and its preparation method is as follows:
[0112] 1. A titanium-containing clay without calcination and a comparative titanium-modified clay, the preparation method of which is as follows:
[0113] 1499 g of halloysite (dry basis) was crushed to an average particle size D (v, 0.5) < 4 μm, 6.9 L of decationized water was added and stirred, 793 g of waste liquid containing titanium tetrachloride was added, the temperature was raised to 90° C., stirred for 2 hours, and the pH value was adjusted to 2.5 with ammonia water to obtain titanium-modified clay DM-1;
[0114] The composition of titanium-modified clay DM-1 is: 83.3 wt% of halloysite (on a dry basis), 16.7 wt% of titanium from waste liquid containing titanium tetrachloride (on a titanium oxide basis), and the solid content of titanium-modified clay is 18 wt%;
[0115] 2. Preparation of anti-metal pollution catalytic cracking additives:
[0116] 0.96 kg of halloysite (dry basis), 1.2 kg of titanium-modified clay DM-1 (dry basis), 0.3 kg of pseudo-boehmite (dry basis), 30 g of aluminum sol (alumina), 60 g of flaky aluminum phosphate PAl-1 (dry basis) and 1.5 kg of deionized water were added to a slurrying tank for slurrying, stirred for 0.5 hour, then 5 mL of hydrochloric acid was added, stirred for 1 hour, and aged at 40° C. for 1 hour. Then 0.486 kg of ammonium dihydrogen phosphate, 90 g of alumina nanofibers (dry basis), 30 g of polyethylene glycol, and 60 g of magnesium oxide were added, mixed and slurried for 1.5 hours, and the obtained slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, spray-dried, and calcined to obtain the comparative auxiliary agent DCAT-3.
[0117] The composition of the additive DCAT-3 is: 32 wt% (dry basis) of halloysite, 40 wt% (dry basis) of titanium-modified clay DM-1, 3 wt% (dry basis) of alumina nanofibers, 2 wt% (dry basis) of sheet aluminum phosphate PAl-1, 10 wt% of alumina from pseudo-boehmite, 1 wt% of alumina from aluminum sol, 10 wt% of phosphorus pentoxide from diammonium phosphate, and 2 wt% of magnesium oxide. The gelled solid content of the additive DCAT-3 is 28%.
[0118] Compared with the additive DCAT-1 prepared in comparative example 1, the additive CAT-4 prepared in Example 4 has a water drop pore volume of 0.30 mL / g due to the addition of titanium-modified clay M-3, alumina nanofibers, flaky aluminum phosphate PAl-1 and carboxymethyl cellulose during the preparation process, which is 50% higher than the comparative additive DCAT-1 (the water drop pore volume is 0.20 mL / g).
[0119] Compared with the additive DCAT-3 prepared in comparative example 3, the additive CAT-2 prepared in example 2 has a smaller wear index, better anti-wear performance and larger pore volume due to the calcination of the clay. Its water drop method pore volume reaches 0.30 mL / g and the wear index is 1.1%, while the water drop method pore volume of the comparative additive DCAT-3 is 0.18 mL / g and the wear index is 8.9%. The wear index of DCAT-3 is too high and cannot meet the use requirements of catalytic cracking additives (generally, the wear index should be less than 3.5%).
[0120] The industrial grade LDO-70 industrial catalyst was mixed with the auxiliary agent CAT-1 prepared in Example 1 and the comparative auxiliary agent DCAT-2 prepared in Comparative Example 2 at a weight ratio of 9:1, and the obtained catalyst mixture and LDO-70 industrial catalyst were respectively contaminated with iron, that is, impregnated with a petroleum ether solution of ferric cyclopentaneate for 1 hour, dried at 120°C, and calcined at 600°C for 2 hours, and 8000μg / g of iron was contaminated on the catalyst mixture. After aging treatment at 800°C and 100% water vapor for 10 hours, the catalytic cracking reaction performance was evaluated on a heavy oil micro-reactor evaluation device (ACE), and the evaluation results are listed in Table 1.
[0121] Among them, total liquid yield = liquefied gas yield + gasoline yield + diesel yield; coke factor = (100-conversion rate) × coke yield / conversion rate.
[0122] Table 1 Catalytic cracking reaction selectivity evaluation results
[0123]
[0124] The results in Table 1 show that compared with the LDO-70 industrial catalyst, when the additive CAT-1 provided by the present invention is used, although the catalyst mixture is contaminated with up to 8000 μg / g of iron, it still has a higher conversion rate and total liquid yield, and the conversion rate and total liquid yield are increased by 1.83 percentage points and 1.68 percentage points, respectively, and the hydrogen / methane and coke factors are reduced. This shows that when the additive CAT-1 provided by the present invention is used, the efficient conversion of heavy oil is promoted, the dehydrogenation reaction in the catalytic cracking reaction process is reduced, the coke formation is reduced, and the selectivity of the catalytic cracking reaction is improved. The additive of the present invention has a good effect of resisting heavy metal iron.
[0125] Compared with the LDO-70 industrial catalyst, when the additive DCAT-2 prepared in Comparative Example 2 is used, although the conversion rate and total liquid yield are also improved, the increase is lower than that when the additive CAT-1 provided by the present invention is used, and the hydrogen / methane and coke factors are also higher than those when the additive CAT-1 provided by the present invention is used, indicating that the anti-iron performance of the additive CAT-1 provided by the present invention is better than that of the additive DCAT-2 prepared in Comparative Example 2.
[0126] The industrial grade LDO-70 industrial catalyst was mixed evenly with the additives CAT-1, CAT-2, CAT-3, CAT-4 and CAT-5 prepared in Examples 1-5 at a weight ratio of 9:1, and the obtained catalyst mixture and LDO-70 industrial catalyst were impregnated with 3000 μg / g Ni and 5000 μg / g V (relative to the catalyst), respectively. After the catalyst contaminated with nickel and vanadium was aged at 800° C. and 100% water vapor for 4 hours, the catalytic cracking reaction performance was evaluated on a heavy oil micro-reactor evaluation device (ACE), and the evaluation results are listed in Table 2.
[0127] Among them, total liquid yield = liquefied gas yield + gasoline yield + diesel yield; coke factor = (100-conversion rate) × coke yield / conversion rate.
[0128] Table 2 Catalytic cracking reaction evaluation results
[0129]
[0130] In Table 2, when the additives CAT-1, CAT-2, CAT-3, CAT-4, and CAT-5 prepared in Examples 1, 2, 3, 4, and 5 are mixed with the base agent LDO-70 industrial catalyst at a weight ratio of 9:1, under the condition of V pollution of 5000 μg / g and Ni pollution of 3000 μg / g, they still have a high conversion rate and total liquid yield, the conversion rate is increased by more than 3.50 percentage points, the total liquid yield is increased by more than 1.50 percentage points, the hydrogen / methane and coke factors are reduced, and excellent nickel and vanadium resistance are shown. It is explained that when the additives CAT-1, CAT-2, CAT-3, CAT-4, and CAT-5 provided by the present invention are used, the efficient conversion of heavy oil is promoted, the dehydrogenation reaction in the catalytic cracking reaction process is reduced, the coke generation is reduced, and the selectivity of the catalytic cracking reaction is improved. The additives of the present invention have good resistance to heavy metals Ni and V, and the heavy oil conversion ability of the additives is strong, the coke generation is low, the use is simple, the dosage is small, and the effect is fast.
Claims
1. A metal pollution resistant catalytic cracking aid, which, based on the weight of the metal pollution resistant catalytic cracking aid being 100%, comprises: 4-40% phosphorus calculated as P2O5, 1-15% alumina nanofibers calculated on a dry basis, 1-10% flaky aluminum phosphate calculated on a dry basis, 2-50% titanium-modified clay, 0-30% aluminum compound calculated on an oxide basis, 0-20% alkaline earth metal calculated on an oxide basis, 0-70% clay calculated on a dry basis, 0-10% inorganic support material calculated on an oxide basis; in, The preparation method of the titanium modified clay comprises the following steps: (1) mixing calcined clay, water and titanium tetrachloride solution to obtain a mixture; (2) reacting the mixture at 40-120° C. for 0.5-6 h to obtain the titanium-modified clay; Based on 100% dry weight of the titanium-modified clay, the composition of the titanium-modified clay comprises 7-45 wt % of titanium in terms of oxide, 0.6-40 wt % of aluminum in terms of oxide, and 30-92 wt % of silicon in terms of oxide.
2. The metal pollution-resistant catalytic cracking aid according to claim 1, wherein: Taking the weight of the anti-metal pollution catalytic cracking additive as 100%, the composition includes: 10-30% phosphorus calculated as P2O5, 3-15% alumina nanofibers calculated on a dry basis, 3-8% flaky aluminum phosphate calculated on a dry basis, 5-20% titanium modified clay, 5-25% aluminum compounds calculated on an oxide basis, 1-10% alkaline earth metals calculated on an oxide basis, 5-62% clay calculated on a dry basis, and 0-8% inorganic carrier material calculated on an oxide basis.
3. The metal pollution-resistant catalytic cracking aid according to claim 1 or 2, wherein: The solid content of the titanium modified clay is 10-45wt%; Preferably, based on 100% dry weight of the titanium-modified clay, the composition of the titanium-modified clay comprises 7-30 wt % titanium calculated as oxide, 8-40 wt % aluminum calculated as oxide, and 35-70 wt % silicon calculated as oxide.
4. The metal pollution-resistant catalytic cracking aid according to claim 1 or 2, wherein: In the preparation method of the titanium-modified clay, the mixed raw materials also include a dispersant; based on the dry basis of the titanium-modified clay being 100%, the content of the dispersant is less than 10%.
5. The metal pollution-resistant catalytic cracking aid according to claim 1 or 2, wherein: In the preparation method of the titanium modified clay, the titanium tetrachloride solution is titanium tetrachloride waste liquid; the titanium tetrachloride waste liquid is waste liquid containing titanium tetrachloride generated in the preparation process of the polypropylene catalyst.
6. The metal pollution resistant catalytic cracking aid according to claim 1 or 2, wherein: In the preparation method of the titanium-modified clay, the clay includes one or a combination of two or more of kaolin, halloysite, montmorillonite, diatomaceous earth, halloysite, sepiolite and bentonite.
7. The metal pollution-resistant catalytic cracking aid according to claim 1 or 2, wherein: In the preparation method of the titanium-modified clay, the calcination is performed at 400-900° C. for 0.5-6 h; Preferably, the preparation method of the titanium modified clay comprises the following steps: mixing clay calcined at 550-850°C for 1-3h, water, and waste liquid containing titanium tetrachloride to form a mixture, heating to 60-120°C and reacting for 0.5-3h to obtain the titanium modified clay.
8. The metal pollution resistant catalytic cracking aid according to claim 1 or 2, wherein: In the preparation method of titanium-modified clay, after the reaction in step (2) is completed, the pH value of the reaction system is 0.5-8. Preferably, the pH value of the reaction system is adjusted to 0.5-8 by using an alkaline substance; Preferably, in step (1), the clay is crushed to an average particle size D(v, 0.5) < 4 μm before or after calcination, and then mixed with water and titanium tetrachloride solution.
9. The metal pollution resistant catalytic cracking aid according to claim 1 or 2, wherein: The phosphorus comes from one or a combination of two or more of phosphoric acid, phosphate, phosphorous acid, phosphite, pyrophosphoric acid, pyrophosphate, polyphosphoric acid, polyphosphate, metaphosphoric acid, and metaphosphate.
10. The metal pollution resistant catalytic cracking aid according to claim 1 or 2, wherein: The alumina nanofiber has a diameter of 20-100 nm, a length of 0.1-5 μm, and a specific surface area of 400 m 2 / g, pore volume ≥1.5cm 3 / g.
11. The metal pollution resistant catalytic cracking aid according to claim 1 or 2, wherein: The preparation method of the flaky aluminum phosphate is as follows: reacting an aluminum compound and a phosphorus compound at a molar ratio of P / Al=(2.6-3.4):1 at 40°C-90°C for 0.1-1h, then reacting at 120°C-170°C for 0.5-3h, drying, and calcining at 400°C-700°C for 0.5-3h to obtain the flaky aluminum phosphate.
12. The metal pollution resistant catalytic cracking aid according to claim 11, wherein: The aluminum compound includes one or a combination of two or more of aluminum oxide, aluminum hydroxide, aluminum sol, and pseudo-boehmite.
13. The metal pollution resistant catalytic cracking aid according to claim 1 or 2, wherein: The clay includes one or a combination of two or more of kaolin, halloysite, montmorillonite, halloysite, and pyrophyllite bentonite.
14. The metal pollution resistant catalytic cracking aid according to claim 1 or 2, wherein: The aluminum compound includes one or a combination of two or more of pseudo-boehmite, boehmite, amorphous alumina, and aluminum sol.
15. The metal pollution resistant catalytic cracking aid according to claim 1 or 2, wherein: The alkaline earth metal includes one or a combination of two or more of magnesium, calcium and barium.
16. The metal pollution resistant catalytic cracking aid according to claim 1 or 2, wherein: The inorganic carrier material includes one or a combination of two or more of zirconium oxide, chloride, nitrate, carbonate, sulfate, oxalate and acetate.
17. The metal pollution resistant catalytic cracking aid according to claim 1 or 2, wherein: The composition of the anti-metal pollution catalytic cracking additive also includes a pore structure improver; the weight of the pore structure improver is less than 10% of the total weight of the anti-metal pollution catalytic cracking additive; Preferably, the pore structure improver includes one or a combination of two or more of 1,3,5-trimethylbenzene, 1,3,5-triisopropylbenzene, methyl cellulose, polyvinyl alcohol, and polyethylene glycol.
18. The method for preparing the metal pollution resistant catalytic cracking aid according to any one of claims 1 to 17, comprising the following steps: (1) mixing and slurrying a phosphorus compound, alumina nanofibers, flaky aluminum phosphate, titanium-modified clay, an aluminum compound, an alkaline earth metal compound, clay, and an inorganic carrier material to obtain a slurry; (2) The slurry is spray-dried to form a shape, and then calcined to solidify, thereby obtaining the anti-metal pollution catalytic cracking aid.
19. The preparation method according to claim 18, wherein: The average particle size D (v, 0.5) of the slurry in step (2) is less than 4 μm.
Citation Information
Patent Citations
Catalytic cracking aid and its preparing method
CN100478420C
Catalytic cracking metal deactivator and its preparation method
CN100540141C
Catalytic cracking addition agent for heavy hydrocarbon oil and preparation method thereof
CN101439303A
Propylene polymerization catalyst
CN102336851B
A catalytic cracking catalyst and its preparation method
CN103769192B